Statistical Literacy Siswa SMP dalam Pembelajaran Matematika - Hariyanti, Firda (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2019)
Information literacy is a student's need to keep pace with the increasingly rapid and dynamic development of science and technology. The ability of statistical literacy becomes a benchmark to find out information literacy students. Statistical literacy is the ability of understanding, interpreting, and evaluating information critically. The ability of statistical literacy is a benchmark in order to know students’ awareness about information. Therefore, it is important to identify students' statistical literacy abilities and how far students are able to use the information in a better way. The aim of this study is to reveal the students’ statistical literacy ability of junior high school students in mathematics class, based on four indicators, (1) understanding the basic terminology of statistics and the probability to understand information; (2) interpreting statistical messages; (3) making conclusion and a decision; (4) evaluating information critically. The research method is descriptive. The subjects of this research are 7th grade students of  SMPN 2 Bangkalan. The results show that, students have good understanding of statistics and probability terminology, students were able to interpret statistical messages in graphical form, but most of the students are weak to interpret data that is presented in the form of pie charts. The ability to evaluate and make a conclusion that is made by most students is not based on mathematical calculations, so that the effect in making decisions is not efficient. The conclusion is the subjects have statistical literacy ability in understanding, interpreting, and making conclusions, but have not reached the stage of evaluating information critically.Melek terhadap informasi merupakan kebutuhan siswa untuk mengimbangi perkembangan IPTEK yang semakin pesat dan dinamis. Kemampuan statistical literacy menjadi tolak ukur untuk mengetahui siswa melek informasi. Adapun statistical literacy merupakan kemampuan memahami, menginterpretasikan, dan mengevaluasi informasi kontesktual secara kritis. Oleh karena itu, pentingnya mengindentifikasi statistical literacy siswa dan sejauh mana siswa dapat menggunakan informasi secara cerdas. Tujuan penelitian ini untuk mengungkapkan kemampuan statistical literacy siswa SMP pada pembelajaran matematika berdasarkan empat indikator, yaitu (1) pemahaman terminologi dasar statistika dan peluang untuk memahami informasi; (2) menafsirkan pesan statistik; (3) menyimpulkan dan membuat keputusan; (4) mengevaluasi informasi secara kritis. Metode penelitian yang digunakan adalah deskriptif. Subjek penelitian adalah siswa kelas VII-D SMP Negeri 2 Bangkalan. Hasil penelitian menunjukkan siswa memiliki pemahaman terminologi dasar statistika dan peluang yang baik, siswa mampu menginterpretasikan pesan statistik dalam bentuk grafik, namun sebagian besar siswa lemah untuk menafsirkan data yang disajikan dalam bentuk diagram lingkaran. Cara mengevaluasi dan penarikan kesimpulan yang dibuat sebagian besar siswa kurang didasari perhitungan secara matematis, sehingga berdampak dalam membuat keputusan yang kurang efisien. Kesimpulannya siswa SMP memiliki kemampuan statistical literacy dalam memahami, menginterpretasikan, dan menarik kesimpulan, namun belum sampai pada tahap mengevaluasi informasi secara kritis.